Endothelial progenitor cells in cardiovascular disorders - Shantsila, Eduard; Watson, Timothy; Lip, Gregory Y H (Journal of the American College of Cardiology, 2007)
The important role of the vascular endothelium in cardiovascular health is increasingly recognized. However, mature endothelial cells possess limited regenerative capacity. There is therefore much interest in circulating endothelial progenitor cells (EPCs) among the scientific community, especially into their purported role in maintenance of endothelial integrity and function, as well as postnatal neovascularization. It has been suggested that these cells might not only be responsible for the continuous recovery of the endothelium after injury/damage, but also might take part in angiogenesis, giving the hope of new treatment opportunities. Indeed, there is accumulating evidence showing reduced availability and impaired EPC function in the presence of both cardiovascular disease and associated comorbid risk factors. Thus, many studies into the potential for use of EPCs in the clinical setting are being undertaken. The goal of this review article is to provide an overview of data relevant to the clinical role of EPCs and perspectives for treatment of cardiovascular disorders.